The new concepts on overcoming drug resistance in lung cancer - Zhang W; Lei P; Dong X; Xu C (Dove Medical Press, 2014)
Weisan Zhang,1 Ping Lei,1 Xifeng Dong,2 Cuiping Xu31Department of Geriatrics, 2Department of Hematology-Oncology, Tianjin Medical University General Hospital, Tianjin, People’s Republic of China; 3Qianfoshan Hospital, Shandong University, Jinan, People’s Republic of ChinaAbstract: Lung cancer is one of the most deadly diseases worldwide. The current first-line therapies include chemotherapy using epidermal growth factor receptor tyrosine kinase inhibitors and radiotherapies. With the current progress in identifying new molecular targets, acquired drug resistance stands as an obstacle for good prognosis. About half the patients receiving epidermal growth factor receptor-tyrosine kinase inhibitor treatments develop resistance. Although extensive studies have been applied to elucidate the underlying mechanisms, evidence is far from enough to establish a well-defined picture to correct resistance. In the review, we will discuss four different currently developed strategies that have the potential to overcome drug resistance in lung cancer therapies and facilitate prolonged anticancer effects of the first-line therapies.Keywords: ALK receptors cancer stem cell, chemotherapy, EGFR-TKI, target therapy, pharmacology, molecular biology, biotherapy